Two dimensional accessibility analysis of metro stations in Xi'an, China. (December 2017) - Li, Linbo; Ren, Huan; Zhao, Shanshan; Duan, Zhengyu; Zhang, Yahua; Zhang, Anming
Highlights: We proposed two dimensions to measure a metro station's accessibility: attraction accessibility and radiation accessibility. We evaluated the attraction accessibility and radiation accessibility of the metro stations of China's Xi'an metro system. We found that attraction accessibility by bus was substantially lower than that by walk. Transfer stations exhibit the highest level of radiation accessibility while the first/last stations have the lowest. Abstract: Two important concepts of accessibility are proposed and measured in this paper: the attraction accessibility and the radiation accessibility. The attraction accessibility means the ease of reaching a given station by using certain modes of transport such as walking, bicycle, bus or taxi. The radiation accessibility represents the ease of reaching other stations from the given station. The metro transit system in Xi'an, China was used as a case study to elaborate the proposed concepts of accessibility. It has been found that the station attraction accessibility depends mainly on the walking connection accessibility, so the improvement of walking environment is a key factor in improving the station's overall accessibility. The transfer stations exhibit the highest level of radiation accessibility while the first/last stations have the lowest. The radiation accessibility of other stations varies widely and depends on their location in the network and the topological depth from the transfer stations. In general, the closer to the middle of the line, the higher the radiation accessibility, whereas the closer to the end of the line, the lower the accessibility. The findings provide decision makers with evidence on how to improve the metro stations' travel environment and the layout of the metro network.